Design and PIC Simulation of Klystron like RBWO with Four Premodulation Cavities - Verma P.; Thottappan M. (My University, 2025)
An X-band Klystron like Relativistic Backward Wave Oscillator, with four pre-modulation cavities, has been designed and simulated for its beam-wave interaction behavior using FDTD-based electromagnetic code. A maximum RF output power of ~2.91 GW at operating frequency of ~9.48 GHz was predicted by the present simulation, given an applied input DC voltage of 570 kV, a beam current of about ~6.7 kA, and a magnetic field of 2.7 T. Other factors such as R/Q, surface power loss, stored electromagnetic energy, and electron power were observed across pre-modulation cavities. The power conversion efficiency was calculated to be ~76% and pulse length of ~100 ns. © 2024 IEEE.